Educational Marketing, School Quality, and Parental School Choice: A Qualitative Case Study of Enrollment Decline in an Indonesian Public Elementary School - Muliasa Azzufar; Lailatussaadah; Nurmayuli; Ainul Mardhiah (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
Parental interest in enrolling children in public primary schools represents a critical indicator of institutional attractiveness and reflects community confidence in educational quality. Despite being located in a densely populated urban area of Banda Aceh, SD Negeri 9 has experienced fluctuating and consistently below-capacity enrollment numbers from 2022 to 2025, raising questions about the factors shaping this trend. This study aims to identify and analyze the internal and external supporting and inhibiting factors that influence new student enrollment interest at SD Negeri 9 Banda Aceh. A descriptive qualitative research design was employed, with data collected through in-depth interviews, observations, and document analysis. Participants were selected using purposive sampling and comprised the school principal, the vice-principal for student affairs, and parents of prospective students. Data were analyzed using SWOT analysis to systematically identify internal strengths and weaknesses alongside external opportunities and threats. The findings reveal that supporting factors include adequate teacher quantity and competency, a conducive physical school environment, progressive adoption of learning technology, and effective information dissemination via social media platforms and parental communication networks. Inhibiting factors include infrastructure deficiencies, the absence of flagship academic programs, limited promotional funding, and intense competition from schools with superior facilities and established reputations. This study contributes empirically grounded insights for school management and education policymakers seeking to strengthen enrollment strategies in public primary schools facing declining applicant trends.